Components of network servers towards improving the effectiveness of e-learning environment - Azzali, Fazli; Mohamed Elias, Ezanee; Daud, Ali Yusny; Harun, Harryizman (2005)
E-learning is the delivery of a learning, training or education program by electronic means. E-learning involves the use of a computer or electronic device (e.g. a mobile phone) in some way to provide training, educational or learning material (Stockly, 2005). Looking at today’s world, the word "e" that stands for electronic has taken over so many aspects of peop1e’s live, hence the importance of e-learning cannot be denied any longer. To be able to implement effective e-learning environment, one of the vital requirements in the whole process is a network server. This paper is a concept paper, which discusses the components of the network server. The idea of this concept was born from an informal observation of Universiti Utara Malaysia’s (UUM) e-learning application environment, Learning Care. Based on the observation, five potential components have been identified. They are course ware template, tools to simplify a development of new course ware, tools for administrations and security purpose, features for interactivity and collaboration, and facilities for adaptation to diversity level of users and learning paradigm. These components will be elaborated in details later in this paper. To set up an effective e-learning environment is very complex considering sixty four variables under five different clusters it affects (Dillon, 2004) and hopefully with the introduction of the five components, the effectiveness of one of the variable can be increased which is the learning environment variable.